Bahasa Inggris - Suci Erawati; Idamawati Idamawati; Hans Wijaya (Postgraduate, University of Mataram, 2023)
Halitosis, known as bad breath, is a condition in which many patients complain about that cause unpleasant odor that comes from the mouth, which can affect the quality of life both psychologically and social life. Knowledge of maintaining oral health plays an important role in oral health conditions. This research to discover whether there is correlation between halitosis and the level of oral hygiene in high school students at Letjen S.Parman school in Medan. Researcher used a descriptive observational method which then analyzed the data using SPSS bivariate analysis with Pearson measuring to analyze the correlation between halitosis and oral hygiene. Shapiro-Wilk test found sig.value amounting to 0.180 on the questionnaire score and 0.068 on the OHIS, both results are greater than 0.05 indicates the datas are normally distributed. Then bivariate analysis was carried out and the Pearson results obtained showed Sig (2 tailed) value of 0.421, where the significance value was Sig.(2 tailed) 0.004<0.05, so can be affirmed that there is a relation between halitosis and the level of oral hygiene. H1 is accepted, which defines that there is an association between halitosis and the level oral hygiene of high school teenagers at Letjen S. Parman Medan school.